(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study aimed to determine the role that the use of educational platforms will play in achieving the educational goals of high school students in the subject of chemistry from the point of view of male and female teachers in light of the Corona pandemic from the point of view of teachers and students to achieve this, the researcher sought to answer the following questions: 1- The extent of the role played by the use of educational platforms in achieving the educational goals of high school students in the subject of chemistry from the teachers’ point of view 2- The extent of the role played by the use of educational platforms in achieving the educational goals of high school students in the subject of chemistry from the teachers’ point of view